CORPORATE SOCIAL RESPONSIBILITY AND FIRM PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Mediaty, Mediaty; Indrijawat, Aini; Panjaitan, Enrico Paul Anggiat; Hamka, Qathrunnada Atikah; Arifin, Andriani (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
CSR refers to a company's commitment to participating in sustainable economic development while remaining mindful of its responsibilities to internal and external stakeholders, such as employees, customers, the community, the environment, and shareholders. CSR is not only about philanthropic activities or donations, but more broadly encompasses ethical policies and practices in conducting business. Several studies have discussed the relationship between Corporate Social Responsibility and Company Value, but there are differences in the results of these studies, which led to this research being conducted. An SLR approach was conducted on 18 articles published between 2017 and 2025. Based on the reviewed literature, the influence of Corporate Social Responsibility (CSR) on company performance is complex and diverse. In many cases, CSR can positively increase company value, reputation, customer satisfaction, and financial performance. However, the impact is not always immediately beneficial, as it depends on the industry context, market conditions, and geographical characteristics where the company operates. Moderating factors such as audit committee expertise, board diversity, and disclosure quality also play an important role in strengthening or weakening the relationship between CSR and company performance.